2016
DOI: 10.3791/54273
|View full text |Cite
|
Sign up to set email alerts
|

Residue-specific Incorporation of Noncanonical Amino Acids into Model Proteins Using an <em>Escherichia coli</em> Cell-free Transcription-translation System

Abstract: The canonical set of amino acids leads to an exceptionally wide range of protein functionality. Nevertheless, the set of residues still imposes limitations on potential protein applications. The incorporation of noncanonical amino acids can enlarge this scope. There are two complementary approaches for the incorporation of noncanonical amino acids. For site-specific incorporation, in addition to the endogenous canonical translational machineries, an orthogonal aminoacyl-tRNA-synthetase-tRNA pair must be provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…If the canonical amino acid is still present within the system, it will be preferably incorporated instead of the noncanonical one [32]. Using the method proposed here, a first expression can be performed to incorporate the residual canonical amino acid into a dummy protein, followed by addition of the corresponding noncanonical amino acid in a second expression reaction.…”
Section: Resultsmentioning
confidence: 99%
“…If the canonical amino acid is still present within the system, it will be preferably incorporated instead of the noncanonical one [32]. Using the method proposed here, a first expression can be performed to incorporate the residual canonical amino acid into a dummy protein, followed by addition of the corresponding noncanonical amino acid in a second expression reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It is still uncertain when and where misincorporation can occur in vivo, though some research suggests that misincorporation of canavanine in place of arginine may happen in the mitochondrial ribosome causing normal protein synthesis to stall [257]. Because misincorporation of BMAA, for one, is blocked in many cases by editing taking place in the mitochoindria [258], [259], a minor level of excitotoxicity of non-coding BMAA, rather than its misincorporation into proteins [243], [254], is believed by some to be causing cell death and contributing to systemic autoimmunities [260], [261].…”
Section: Approaching and Penetrating The Nuclear Envelopementioning
confidence: 99%
“…The residue specific incorporation of non-canonical amino acids into proteins is a far reaching application of cell-free transcription-translation systems. Non-canonical amino acids as a surrogate at canonically prescribed locations can lead to new or improved properties of proteins with potential applications in biochemistry, biotechnology and biomedicine (Worst et al, 2016(Worst et al, , 2015. However, for residue specific incorporation of non-canonical amino acids even small amounts of a corresponding canonical one will preferentially bind at the level of aminoacyl-tRNA-synthetases (Worst et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Non-canonical amino acids as a surrogate at canonically prescribed locations can lead to new or improved properties of proteins with potential applications in biochemistry, biotechnology and biomedicine (Worst et al, 2016(Worst et al, , 2015. However, for residue specific incorporation of non-canonical amino acids even small amounts of a corresponding canonical one will preferentially bind at the level of aminoacyl-tRNA-synthetases (Worst et al, 2016). Experiments by Hopfield have shown that a mechanism termed kinetic proofreading leads to a discrimination of up to 1/1000 against the incorrect amino acid (Hopfield, 1974;Hopfield et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation